Synthesis and Derivatization of Diaminobenzene Fluorophores with Amine Protecting Groups - Kim, Haein; Kim, Dopil; Kim, Jun Yeong; Lee, Sangho; Yang, Won-Geun; Kim, Dongwook; Kim, Ki Tae; Kim, Dokyoung; Park, Myung Hwan; Kim, Min (Synthesis, 2024)
Introducing two electron-donating groups and two electron-withdrawing groups together in symmetrical positions on the benzene ring is a fundamental way to synthesize and prepare single-benzene-based fluorophores (SBBFs). Their photophysical properties are adjusted through the electronic and structural properties of the functional groups. Reported herein is the functionalization of diaminobenzene derivatives with various amine protecting groups, including amides, urea, carbamates, and sulfonamides. Both absorption and emission properties of the obtained SBBF molecules were carefully investigated. Sequential and unsymmetric diamine protections were also explored with diaminobenzene derivatives for fine-tuning of the molecular properties.
Keywords: single-benzene-based fluorophores; protecting groups; diaminobenzenes; photoluminescence